2020
DOI: 10.1016/j.jvs.2019.08.253
|View full text |Cite
|
Sign up to set email alerts
|

High plasma microfibrillar-associated protein 4 is associated with reduced surgical repair in abdominal aortic aneurysms

Abstract: Objective: Identifying biomarkers for abdominal aortic aneurysms (AAA) could prove beneficial in prognosis of AAA and thus the selection for treatment. Microfibrillar-associated protein 4 (MFAP4) is an extracellular matrix protein that is highly expressed in aorta. MFAP4 is involved in several tissue remodeling-related diseases. We aimed to investigate the potential role of plasma MFAP4 (pMFAP4) as a biomarker of AAA. Methods: Plasma samples and data were obtained for 504 male AAA patients and 188 controls in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…However, the pattern of MFAP4 regulation has shown inconsistency (47)(48)(49), and a role of MFAP4 in clinical AAA remains unknown. We have recently shown that high plasma MFAP4 is associated with reduced risk of undergoing later surgical repair in AAA (50); however, this observation needs validation in an independent cohort.…”
Section: Discussionmentioning
confidence: 86%
“…However, the pattern of MFAP4 regulation has shown inconsistency (47)(48)(49), and a role of MFAP4 in clinical AAA remains unknown. We have recently shown that high plasma MFAP4 is associated with reduced risk of undergoing later surgical repair in AAA (50); however, this observation needs validation in an independent cohort.…”
Section: Discussionmentioning
confidence: 86%
“…Microfibrillar-associated protein 4 (MFAP4), known as 36-kDa microfibril-associated glycoprotein (MAGP36), is ubiquitously distributed in the extracellular matrix of the human body ( Toyoshima et al, 2005 ; Schlosser et al, 2006 ). MFAP4 has been associated with immune response ( Niu et al, 2011 ), liver fibrosis ( Madsen et al, 2020 ), renal fibrosis ( Pan et al, 2020 ), atherosclerosis ( Wulf-Johansson et al, 2013 ), pulmonary airspace enlargement ( Holm et al, 2015 ), and abdominal aortic aneurysms ( Lindholt et al, 2020 ). MFAP4 was also found to be involved in human cancers, such as pancreatic adenocarcinoma ( Guerrero et al, 2021 ), serous OC ( Zhao et al, 2019 ), breast cancer ( Yang et al, 2019 ), and lung cancer ( Feng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that upregulation of MFAP4 is a compensatory response to the abnormal elastin formation in Marfan syndrome patients, and lower MFAP4 protein expression in abdominal aortic aneurysm reflects the increased expression of proteases or the loss of contractile vascular smooth muscle cells. 72 , 75 On Day 21, HAoSMCs that underwent rhythmic strain (D21-strain) exhibited enhanced expression of contractile phenotypic marker ACTA2, which was comparable to that in normal aortic tissues. OPN, ELN, MFAP4, TIMP1, and MAPK1 were also comparably expressed on the dynamic microphysiological models and in normal aortic tissues.…”
Section: Resultsmentioning
confidence: 92%